2016
DOI: 10.18632/oncotarget.10246
|View full text |Cite
|
Sign up to set email alerts
|

Post-translational deregulation of YAP1 is genetically controlled in rat liver cancer and determines the fate and stem-like behavior of the human disease

Abstract: Previous studies showed that YAP1 is over-expressed in hepatocellular carcinoma (HCC). Here we observed higher expression of Yap1/Ctgf axis in dysplastic nodules and HCC chemically-induced in F344 rats, genetically susceptible to hepatocarcinogenesis, than in lesions induced in resistant BN rats. In BN rats, highest increase in Yap1-tyr357, p73 phosphorylation and Caspase 3 cleavage occurred. In human HCCs with poorer prognosis (< 3 years survival after partial liver resection, HCCP), levels of YAP1, CTGF, 14–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 61 publications
(89 reference statements)
1
21
0
Order By: Relevance
“…As shown in Table , heterogeneity analysis of the relationship between YAP expression and AFP indicated no significant heterogeneity among the studies. YAP is involved in many signalling pathways associated with HCC, but its actual role is unclear and worthy of investigation, especially because Simile's group reported that upregulation of YAP is related to HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Table , heterogeneity analysis of the relationship between YAP expression and AFP indicated no significant heterogeneity among the studies. YAP is involved in many signalling pathways associated with HCC, but its actual role is unclear and worthy of investigation, especially because Simile's group reported that upregulation of YAP is related to HCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…YAP increases glycolysis [ 179 ] and supports the expression of Glut3, a known driver of a cancer stem cell phenotype, whose expression is elevated in cancer [ 18 , 182 ]. YAP/TAZ/TEAD and AP-1 form a complex that synergistically activates target genes controlling S-phase entry and mitosis [ 183 ]. In addition, in HepG2, Huh7, and Hep3B cells, forced YAP1 over-expression results in the expression of stem cell markers and increases cell viability [ 182 ].…”
Section: The Warburg Effect and Tumor Therapymentioning
confidence: 99%
“…Activates p53 in response to mitotic stress 53,[142][143][144]149 Activates p53 in response to oncogenic Ras 117,118 Activates p53 in response to excess cholesterol 156 Activates p53 during mESC differentiation 52 YAP Loss of YAP induces p53 145,147,148 YAP represses ΔNp63 to inhibit lung cancer squamous cells transdifferentiation. 182 YAP-p73 promotes apoptosis 106,108-110, 132-134, 136,183 Yki inactivation induces Dmp53 119 p63 inhibits p73-YAPdependent apoptosis 22,137 YAP-tyr357-p73 is a marker for well differentiated HCC 85 Yki binds Dmp53 to promote apoptosis 131 YAP positively regulates p63 in epidermal stem cells 66 Locus is amplified in p53 null tumors [75][76][77]184,185 YAP positively regulates p63 in airway epithelium 71 p53 and YAP antagonistically regulate FOXM1 [186][187][188] YAP-p63 block differentiation in HNSCC 86 p53 transactivates 14-3-3σ, which inhibits YAP/TAZ 124,125 Binds p63 and prevents its degradation 88,89 YAP and p53 cooperate in apoptosis and senescence [126][127][128] Hyperactivation of YAP/TAZ induces p53 152,154 YAP and mutp53 cooperate in transformation 33,82 Mutp53 induces miRs that tar...…”
Section: Lats2mentioning
confidence: 99%
“…83 Interestingly, different post-translational modifications, which have been shown to govern YAP stability, may dictate the differentiation status of HCC. 84,85 Although hyperactivity of the YAP-TEAD functional axis predicts poor prognosis and stemness characteristics in HCC, tumors in which YAP is modified to interact with p73 (p-Y357) display more apoptotic markers and have better prognosis. 85 Thus, YAP can promote either tumor cell death or tumor-initiating properties, depending on its regulatory interactions with different members of the p53 family.…”
Section: Cancer Stem Cellsmentioning
confidence: 99%
See 1 more Smart Citation